(untitled) (Journal of Educational Sciences, 2021)
Currently, the issues of digital transformation of education remain relevant, which is associated with the socio-political conditions of life in modern society.During the period of distance learning, the need to create and design video lessons and online lessons in real time increases. Designing these types of activities involves the use of pedagogical design as a process of analyzing learning needs and goals. The aim of the study is to identify the role of pedagogical design using the ADDIE model in the design of components of online lessons in Russian language and literature in a comprehensive school. The article summarizes the points of view of researchers regarding the term "pedagogical design", reviews the scientific literature, describes models for designing video and online lessons. On the example of using the model of pedagogical design ADDIE, forms of designing educational material in the Russian language are proposed, built in the form of simulators - interactive tasks with automatic verification of the answer. The value of the study is that the results obtained can be used in the design of video components and online lessons in the Russian language and literature in a comprehensive school. The authors of the article pay special attention to pedagogical design as a process in the development of technical specifications when designing the content of online lessons, digital content, simulators and educational multimedia tools. Keywords:pedagogical design, ADDIE model, designing online lessons, Russian language and literature